Design of Miniaturized Filtering Power Dividers for System-in-a-Package - Chen, Chi-Feng; Huang, Ting-Yi; Shen, Tze-Min; Wu, Ruey-Beei (IEEE transactions on components, packaging, and manufacturing technology (2011), 2013)
Miniaturized power dividers with high-selectivity bandpass behavior are presented and analyzed theoretically in this paper. Based on the coupled-resonator topology, the circuit area of the proposed power divider can be reduced as the size of the assembled resonators shrinks. Therefore, in order to effectively reduce the circuit area and improve the stopband performance, the net-type resonator is selected to design the filtering power dividers. For demonstration, power dividers with Chebyshev- and quasi-elliptic bandpass responses have been designed and fabricated with microstrip in printed circuit boards. The highly symmetric structure of each power divider provides a low in-band magnitude and phase imbalances. Consequently, the proposed filtering power dividers have advantages of small size, sharp skirt selectivity, high isolation, and superior out-of-band performance. All measured results are in good agreement with the full-wave simulation results.